2018
DOI: 10.1155/2018/1473706
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive Bismuth-Film Electrode Supported on Pencil-Lead Graphite for Determination of Pb(II) and Cd(II) Ions by Anodic Stripping Voltammetry

Abstract: The present work reports the development and application of bismuth-film electrode (BiFE), obtained by in situ method on the pencil-lead graphite surface, for simultaneous Cd(II) and Pb(II) determination at trace levels, as alternative to replace the mercury-film electrodes. Experimental factors, deposition time (td), deposition potential (Ed), and Bi(III) concentration (CBi), were investigated by applying a 23 factorial design using 0.10 mol/L acetate buffer solution (pH 4.5) as supporting electrolyte. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…BiFE and other metal film electrodes (PbFE, SnFE and SbFE) introduction to electrochemical detection was considered a landmark in the research of "green" electrode materials for stripping analysis towards sensing Cd 2+ , Pb 2+ , Tl 2+ , Cu 2+ and Zn 2+ , 84 although they need polishing and surface renewal steps prior to its use, which makes them highly dependent on the experimentalist. 85,86 Banks et al 57 deposited Bi, Sb, Sn films on SPEs as well as classic electrode platforms (BDD and GC) and tested the platforms towards the detection of Cd 2+ and Pb 2+ . Interestingly, they found that unmodified SPEs are capable of detecting both analytes at WHO levels, without any electrode pre-treatment (prior use, polishing and/or electrochemical treatment/surface-or bulk-modification).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…BiFE and other metal film electrodes (PbFE, SnFE and SbFE) introduction to electrochemical detection was considered a landmark in the research of "green" electrode materials for stripping analysis towards sensing Cd 2+ , Pb 2+ , Tl 2+ , Cu 2+ and Zn 2+ , 84 although they need polishing and surface renewal steps prior to its use, which makes them highly dependent on the experimentalist. 85,86 Banks et al 57 deposited Bi, Sb, Sn films on SPEs as well as classic electrode platforms (BDD and GC) and tested the platforms towards the detection of Cd 2+ and Pb 2+ . Interestingly, they found that unmodified SPEs are capable of detecting both analytes at WHO levels, without any electrode pre-treatment (prior use, polishing and/or electrochemical treatment/surface-or bulk-modification).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…On the other hand, the OC combined value for 1.94Bi was determined to be 0.009410. BiFE is considered to be one of the benchmarks regarding in situ FEs in the electroanalysis of heavy metal traces [1,8,12,[41][42][43][44][45][46][47]. Therefore, the importance of this work is signified with the OC combined value for 1.00Bi0.60Sn0.34Sb, which is at least one order of magnitude better (higher), thus demonstrating the improved design of the in situ FE when using this combination of ions to form an in situ FE compared to the use of only one ion to form a pure in situ FE.…”
Section: Interference Studymentioning
confidence: 99%
“…However, given the toxicity of mercury vapor and salts [14,15], the study of alternative materials may involve high toxicity. Several studies have shown that bismuth and antimony film electrodes have excellent reduction performance comparable to mercury electrodes [16,17]. Critically, both Sb(III) and Bi(III) have low toxicity and are environmentally friendly [10,18].…”
Section: Introductionmentioning
confidence: 99%